Individual Entrepreneurial Orientation Impact on Entrepreneurial Intention: Intervening Effect of PBC and Subjective Norm - Awang, Amran; Amran, Shazwani; Niza Md Nor, Mohamad; Ibrahim, Ima Ilyani; Mohd Razali, Mohd Fazly (Journal of Entrepreneurship, Business and Economics; Vol 4 No 2 (2016), 2016)
This study focuses on the intervention of attitude towards entrepreneurship, participation in entrepre-neurial education, perceived behavioral control (PBC) and subjective norm on the relationship be-tween students’ grade and individual entrepreneurial orientation (EO) in influencing students’ entre-preneurial intention (EI). The paper verifies theory of planned behavior (TPB) explaining a public university students in Malaysia. Empirical evidence was derived from a quantitative approach based on a cross sectional study among 202 students. Hypothesis testing utilizes multiple regression analysis verifing the direct and mediated relationships. The study suggests that students grade, individual EO comprises of proactive personality and risk taking propensity were proven important in explaining attitude towards entrepreneurship, participation in entrepreneurship education, PBC and subjective norm. On the other hand, individual EO, PBC and subjective norm directly explained EI. Subsequent-ly, PBC and subjective norm proved as significant mediators in individual EO and EI relationships. The results shall aid the university management in formulating their curriculum and programs that fit students’ priorities in shaping their future undertaking as an entrepreneur. Malaysian public policy regarding higher education should consider some mindset reformation required in higher learning institutions’ entrepreneurship curriculum in the country. Annual budget for higher learning institu-tions’ entrepreneurship programs shall be allocated accordingly after considering the results of the study. Research paper Reference to this paper should be made as follows: Awang, A., Amran, S., Md Nor, M. N., Ibrahim, I. I., Mohd Razali, M. F. (2016). ―Individual Entrepreneurial Orientation Impact on Entrepreneurial Intention: Intervening Effect of PBC and Subjective Norm‖, Journal of Entrepreneurship, Business and Economics, Vol. 4, No. 2, pp. 94–129.